RELEVANCIA DE LA GESTIÓN DE MARCAS DENTRO DE LOS GRADOS DE PUBLICIDAD, COMUNICACIÓN PUBLICITARIA, CORPORATIVA, Y MARKETING EN LA UNIVERSIDAD ESPAÑOLA - Dr. Santiago MAYORGA ESCALADA (Fonseca, Journal of Communication, 2023)
This work attempts to validate or refute a working hypothesis raised around the relevance of brand management, under-stood as its own subject, Within the Degrees of Advertising and Public Relations, Advertising and Corporate Commu-nication, and Marketing at the Spanish university